Workflows and service discovery: a mobile device approach - Holthausen, Ricardo; Díaz-del-Pino, Sergio; Perez-Wohlfeil, Esteban; Rodríguez-Brazzarola, Pablo; Trelles-Salazar, Oswaldo Rogelio (Springer, Cham, 2018)
Bioinformatics has moved from command-line standalone programs to web-service based environments. Such trend has resulted in an enormous amount of online resources which can be hard to find and identify, let alone execute and exploit. Furthermore, these resources are aimed -in general- to solve specific tasks. Usually, this tasks need to be combined in order to achieve the desired results. In this line, finding the appropriate set of tools to build up a workflow to solve a problem with the services available in a repository is itself a complex exercise. Issues such as services discovering, composition and representation appear. On the technological side, mobile devices have experienced an incredible growth in the number of users and technical capabilities. Starting from this reality, in the present paper, we propose a solution for service discovering and workflow generation while distinct approaches of representing workflows in a mobile environment are reviewed and discussed. As a proof of concept, a specific use case has been developed: we have embedded an expanded version of our Magallanes search engine into mORCA, our mobile client for bioinformatics. Such composition delivers a powerful and ubiquitous solution that provides the user with a handy tool for not only generate and represent workflows, but also services, data types, operations and service types discovery
Keywords: Bioinformática - Congresos; mORCA; Magallanes; Search engine; Workflow generation; Mobile devices